Motor output matters: Evidence of a continuous relationship between Stop/No-go P300 amplitude and peak force on failed inhibitions at the trial-level - Nguyen, An T.; Albrecht, Matthew; Lipp, Ottmar; Marinovic, Welber (2020)
© 2020 Society for Psychophysiological Research Motor actions can be suppressed with varying degrees of success, but this variability is not often captured as responses are typically represented as binary (response vs. no-response). Although the Stop/No-go P300 has been implicated as an index of inhibitory-control, it is unclear how the range of motor outputs relates to the P300. We examined the nature of this association in two experiments using an Anticipatory Timing and a Go/No-go Task, while measuring peak force, movement onset time, and P300. In both experiments, our results showed that trial-by-trial P300 amplitude on Failed Inhibitions were continuously related to peak force, where higher force (reflecting a greater degree of error) was associated with smaller P300 amplitude. Compared to Successful Inhibitions, P300 amplitude and onset latency on Failed Inhibitions were significantly reduced and delayed. Although the binary categorization of inhibition-success (Successful vs. Failed) accounts for significant variance in the P300, it misses a reliable linear relationship that can be captured by continuous measures of motor output. Overall, the results provide evidence that P300 may reflect the continuously varying engagement of inhibitory-control. We present an activation model to visualize the P300-force association and to illustrate how motor output might be modeled in the context of inhibitory-control. Our results highlight the relevance of P300 amplitude and the importance of studying the spectrum of motor output and the need for future models to account for motor output.